Autonomic Modulation for the Treatment of Ventricular Arrhythmias: Therapeutic Use of Percutaneous Stellate Ganglion Blocks. (11th January 2017) - FUDIM, MARAT; BOORTZ‐MARX, RICHARD; PATEL, CHETAN B.; SUN, ALBERT Y.; PICCINI, JONATHAN P.
Stellate Ganglion Block for Ventricular Arrhythmia: Ventricular tachycardia (VT), ventricular fibrillation (VF), and electrical storm are commonly encountered emergency conditions in cardiac and surgical intensive care units. In most cases, recurrent ventricular arrhythmias or electrical storm are associated with a heightened sympathetic tone. These arrhythmias can be difficult to treat and may be refractory to beta‐blockade, antiarrhythmic therapy, sedation, and mechanical hemodynamic support. While monomorphic ventricular tachycardia and PVC‐triggered polymorphic ventricular tachycardia may sometimes be amenable to successful ablation, some patients may be too critically ill to make such an approach feasible. We present 2 cases of minimally invasive stellate ganglion blocks for the treatment of electrical storm in patients with advanced heart failure on mechanical life support. These cases are part of a collaborative initiative at our institution to use percutaneous stellate ganglion block as an adjunctive intervention to achieve control of life‐threatening ventricular arrhythmias.